A Combined 25Mg Solid‐State NMR and Ab Initio DFT Approach to Probe the Local Structural Differences in Magnesium Acetate Phases Mg(CH3COO)2 ⋅ nH2O (n=0, 1, 4). Issue 14 (8th May 2018) - Seymour, Valerie R.; Day, Stephen P.; Scholz, Gudrun; Scheurell, Kerstin; Iuga, Dinu; Griffin, John M.; Kemnitz, Erhard; Hanna, John V.; Smith, Mark E.
Abstract: Multinuclear ( 1 H, 13 C, 25 Mg) solid‐state NMR data is reported for a series of magnesium acetate phases Mg(CH3 COO)2 ⋅ nH2 O (n=0 (two polymorphs), 1, 4). The central focus here is 25 Mg as this set of compounds provides an expanded range of local magnesium coordinations compared to what has previously been reported in the literature using NMR. These four compounds provide 10 distinct magnesium sites with varying NMR interaction parameters. One of the anhydrous crystal structures (α) has an MgO7 site which is reported, to the best of our knowledge, for the first time. For those phases with a single crystal structure, a combination of magic angle spinning (MAS) NMR at high magnetic field (20 T) and first principles density functional theory (DFT) calculations demonstrates the value of including 25 Mg in NMR crystallography approaches. For the second anhydrate phase (β), where no single crystal structure exists, the multinuclear NMR data clearly show the multiplicity of sites for the different elements, with 25 Mg satellite transition (ST) MAS NMR revealing four inequivalent magnesium environments, which is new information constraining future refinement of the structure. This study highlights the sensitivity of 25 Mg NMR to the local environment, an observation important for several sub‐disciplines of chemistry where the structural chemistry of magnesium is likely to be crucial. Abstract : Structural Insight : 25 Mg Solid‐state MAS NMR spectra for α‐ and β‐Mg(OAc)2 were obtained (see picture), providing NMR parameters for an MgO7 site within a known structure, and providing structural insight for a phase with no known crystal structure.